Intra-arterial administration of cell-based biological agents for ischemic stroke therapy. (4th March 2019) - Spiliopoulos, Stavros; Festas, Georgios; Reppas, Lazaros; Brountzos, Elias
ABSTRACT: Introduction : Ischemic stroke is becoming a primary cause of disability and death worldwide. To date, therapeutic options remain limited focusing on mechanical thrombolysis or administration of thrombolytic agents. However, these therapies do not promote neuroprotection and neuro-restoration of the ischemic area of the brain. Areas covered : This review highlights the option of minimal invasive, intra-arterial, administration of biological agents for stroke therapy. The authors provide an update of all available studies, discuss issues that influence outcomes and describe future perspectives which aim to improve clinical outcomes. New therapeutic options based on cellular and molecular interactions following an ischemic brain event, will be highlighted. Expert opinion : Intra-arterial administration of biological agents during trans-catheter thrombolysis or thrombectomy could limit neuronal cell death and facilitate regeneration or neurogenesis following ischemic brain injury. Despite the initial progress, further meticulous studies are needed in order to establish the clinical use of stem cell-induced neuroprotection and neuroregeneration.